Impact of consumer information capability on green consumption intention: the role of green trust and media publicity - Luo, Gong-Li; Zheng, Hao; Guo, Yan-Lu (Frontiers in Psychology, 2023)
In the context of the digital information era, consumers' information capability plays a crucial role in shaping their green consumption intention. To delve deeper into the dynamics of how information capability influences consumers' green consumption intention, this study constructs a theoretical model grounded in information asymmetry theory and cognitive bias theory. Additionally, the mediating role of green trust and the moderating role of media publicity are incorporated to comprehensively investigate the influence mechanism of information capability on consumers' green consumption intention. Empirical analysis is conducted based on data collected through a questionnaire survey. The findings of this study reveal that information capability exerts a partially mediating effect on consumers' green consumption intention. Specifically, information capability directly influences consumers' green consumption intention, and it also indirectly impacts their green consumption intention through its influence on green trust. Furthermore, media publicity positively moderates the relationship between information capability and consumers' green consumption intention. This research contributes to the existing literature by enhancing our understanding of the influence pathway leading to green consumption intention. Its insights offer valuable implications for promoting green consumption and advancing sustainable development initiatives.